Boolean Postulates and Laws: o e e Va A e
Boolean Postulates and Laws: o e e Va A e
Boolean Postulates and Laws: o e e Va A e
S~~ to mathematical algebra, boolean algebra also uses postulates and laws in order h."
sunplify the expression. Some of the postulates and laws are as given below:
1. Properties of O and 1: You are aware that the value of any boolean variable 1nay eith~r
be O or 1. Hence, 1 added to the variable results in 1 and O multiplied to a variable
results in O.
A+l=l
A·O=O
Truth tables to illustrate these equations are given below:
'" A 1 A+.1 A 0 A·O
"
0 1 1 0 0 0
1 l 1 1 0 0
Similarly, 0 added to a variable and 1 multiplied to the variable results in t.h e same
Variable.
A+ O=A
A- l = A
21 fjoolean Alge~ra - ~
Truth tables to illustrate these equations are as given below:
I ~ I ~ II
A 0 A+O
0 0 0 A~l
1 0 1 1 1 ,.
2. Complementary law: This law sta tes th a t when a variabl e is added to its complement
resul ts in 1 and the va riable mulliplied w ith its comp lem ent res ults in 0.
A+ A ' =1
A.A'=O
Truth tables to illu strate these equa tions arc given be low :
A A' A+ A' A A' A · A'
0 1 1 0 1 0
1 0 1 1 0 0
3. Idempotent law: This law sta tes that when a variabl e is e ith e r added or multiplied
with same variable w ill res ult in the same variable.
A + A=A
A.A .= A
Truth tables to illustrate these equations are given below:
I ~ I ~ I A~A I I~ I ~ I A~A
1 1 1 1 1 1
4. Involution law: This law states that double complement of any variable results in the
same variable.
(A')' =A
Truth table to illustrate this equation is as given below:
A A' (A')'
0 1 0
1 0 1
A B A.B A B 8.A
--
0 0 0 0 () 0
0 ] 0 () 1 0
1 0
· '-
--
() 0
·1 1
- ., - ·1
I 0
I 'I
•
-
'1 1'
I
I_
-
1 1 1 1 1 1 1 I 1
Proof of the second law: 1' , 1'
A+BC=(A+B)(A+C)
• By using algebraic method:
R.H.S = (A+ B)(A + C)
Multiplying both the terms, we get
= A·A+A ·C+A ·B+B ·C
= A+A·C+A ·B+B · C [A·A=A]
= A(l + C + B) + B · C [ Take A Common l
= A ·l + BC [ 1 + C + _B =1 + B =1]
= A·l + BC [A ·l=A]
= A+BC
Hence, R.H.S = L.H.S
Hence proved.
• By using truth table:
7.
1 1
Associative law.
1 1 1
1'
1
- 1 1
1'
' This law allows the removal of brackets from an expression and regrouping of the
variables. Thus, the output/ result is unchanged. Each of the Boolean laws are explained
with just a single or two variables, but the number of variables defined by a single
law is not limited to this as there can be an infinite number of variables as inputs too
lhe expression. This law can be used to prove any given Boolean expression and for
simplify ing complicated digital circuits. This law can further be explained into two
fom1s:
• First law : A + (B + C) = (A + B) + C
• Second law : A· (B · q ·= (A · B) · C
Proof of the first law by using truth table:
A B C B+ C A+(B+C) A +B (A + B) +C
0 0 0 0 0 0 0
0 0 1 1 1 0 1
0 1 0 1 1 1 1
0 1 1 1 1 1 1
1 0 0 0 1 1 1
1 0 1 1 1 1 1
1 1 0 1 1 1 1
1 1 1 1 1
....
1 1
A.(B.C)
-
(A.B) (A.B).C
1'
0 0 0 0 0 0 0
0 0 1 0 0 0 0
0 1 0 0 0 0 0
0 1 1 1 0 0 0
1 0 0 0 0 0 0
1 0 1 0 0 0 0
1 1 0 0 0 1 0
1 1 1 1 1 1 1
1' /J'
8. Absorption law: This law states that:
• First law : A + A · B= A
• Second law: A (A + B) = A
First law can be proved in two ways as given below:
• By using algebraic method
L.H.S=A+AB
= (A + A)(A + B) [Use Distributive Law]
= A(A + B) [A + A= A, Idempotent law]
= A·A+A · B [A · A=A]
= A+AB [Take A Common]
=A(l + B) [1 + B=l]
=A · l [A · l=A]
=A
Hence proved.
• By using truth table:
A B A·B . A:+A• Jr
0 0 0 0
0 1 0 0
1 0 0 1
,,,
1 1
.... 1
,,,
1
-
Second law can also be proved in two ways as given below:
• By using algebraic method:
A (A + B)=A
L.H.S === A(A + B)
=== A·A + A-B
=== A+ AB
=== A(l + B) [A-A=== A]
=== A-1 [Taking A common]
=== A [1 + B === 1]
L.H.s === R.H.s [A-1 === A]
Hence proved.
• By using truth table:
A B A+B A.(A + B)
0 0 0 0
0 1 1 0
1 0 1
Demorgan's Theorem
1
1'
1
...
.._,
1
1
1
_T
Augustine Demorgan, a great mathematician, developed two theorems which have brought
immense utilities in boolean algebra. This law states that the complement of sum of the
variables is same as product of the complements of the variables and vice-versa.
• First law: (A + B)' =A'· B'
• Second law: (A· B)' = A' + B'
Proof of the first law:
• By using algebraic method
(A+B}'=A'·B' . .
You know that the sum of a variable and its complement is 1 and their product 1s 0.
The theorem states that A' •B' is complement of A + B. To prove, it must satisfy:
(i) (A + B)(A' · B') =0 and (ii) (A + B) + (A' ·B') =1
Consider the first case:
(A + B)(A' · B') = 0
L.H.S = (A+ B)(A' · B')
= A·A' · B' + B·A'B'
= O. B' + O. A' [ A ·A'= 0 and B · B' = OJ
= 0 + 0=0
Second case:
(A+ B) + (A' ·B')=l
L.H.S = (A+ B) +(A'. B') I
.-..
1 1 1 0 0 0 0
·1 I
Proof of the second law:
This law states that
(A · B)' = A' + B'
From the truth table shown above, columns (A• B)' and A' + B' have same entries. Hence,
it is proved that (A· B)' = A' + B'.
Demorganization: Application of Demorgan' s theorems brings changes in the operators
in any boolean expression. It also breaks the whole complement of any expression into
individual complement of the variables.
For example,
(A(A + B))' = A' +(A+ B)' = A' + A'.B'
In the example shown above, the breaking of whole complement causes individual
complement of the variables and also brings changes in the signs, i.e., a ( + ) sign gets
converted to a ( •) and a ( •) sign to a ( + ). This process is called demorganization and it
works on the principle of "Breaking the complement and changing the sign" .
Principle of duality: Demorganization supports changing of the signs in the boolean
expression. Hence, from a given boolean expression you can obtain another boolean
expression by replacing each plus ( + ) sign with a· dot ( •) and each dot (.) sign With a plus
( + ), each 1 with O and each O with 1. The variables must remain same during the process.
The expression, so obtained, is known as dual expression of the given boolean expression
and the process of conversion is termed as Principle of duality.
'
In order to obtain dual relation, use the following step"!;:
• Write the given relation. ,
•· Let the variables as it is (i.e., complement and non-complement variables must remain
I
same).
• Convert each plus sign into dot.
• Convert each dot sign into plus.
• Convert each 1 into 0.
• Convert each O i ·nto 1.
The relation, so obtained, is the dual of the given relation.